Nodular Hidradenoma of the Lower Limb in a Young Female Impersonating as Sebaceous Cyst - Shetty, Archana; Gnanadev, Praveen; Gaffoor, Nidha; Murali, Nirupama (Journal of Health and Allied Sciences NU, 2022)
Adnexal tumors possess a remarkable capacity for morphological diversity and often present with nonspecific clinical presentations. Definitive diagnosis is made on histopathology with categorization based on the predominant morphological component. We present a case of a 31-year-old woman, with a swelling in the upper one-third of the right leg suspected clinically to be an infected sebaceous cyst. Histopathological examination clinched the diagnosis of a nodular hidradenoma. We wish to present this case not only for its uncommon clinical presentation but also for the diverse spectrum of histomorphological features that can be exhibited by this tumor. The case also emphasizes to surgeons the importance of complete surgical resection given the chances of recurrence and rare cases of malignant transformation associated with this entity.
Keywords: adnexa; hidradenoma; sebaceous; skin